Accelerating performance : how organizations can mobilize, execute, and transform with agility - Price, Colin; Toye, Sharon, 1964- (Hoboken : Wiley, 2017)
"Transform your organization into a dynamic catalyst for success Accelerating Performance is not just another “warm and fuzzy” change management book—it's a practical, comprehensive, data-driven action plan for picking up the pace and achieving more. Written by the one of the authors of Beyond Performance, this book draws on a combination of empirical research and decades of experience advising global companies to show you how to reduce time to value by building and changing momentum more quickly than your competitors. The META framework (short for mobilize, execute, and transform with agility) offers advice for leading change at four levels: strategy, the organization, teams, and individuals. In addition to step-by-step guidance toward assessment, planning, and implementation, the book offers: A diagnostic tool for leaders, teams, and organizations to assess their starting place, and highlight the specific areas needed to improve the ability to accelerate performance. A detailed look at the factors proven to create drag—and drive—at each of the four levels: strategy, organizations, teams, and individuals. An exploration of the 39 differentiating actions that organizations can combine as dictated by their strategy and context into a winning recipe. A closer look at the practices of 23 “superaccelerators,” a global (and perhaps unexpected) mix of companies that have demonstrated a consistent ability to accelerate performance. A single taste of success is all it takes to spark change, but the hard work of following through requires constant vigilance—and a plan. Learn how to capture that drive, bottle it, and use it to sustain motivation, inspiration, and achievement. Deliver at the highest level, and then turn around and do even better next time. Accelerating Performance gives leaders a step-by-step framework for taking action and transforming their organizations, teams, and even themselves, starting today"--
Machine generated contents note: Foreword Introduction Acknowledgments About the Authors Section 1: Move Fast or Die Faster Chapter 1: The Soft Stuff Really Is the Hard Stuff Chapter 2: How to Increase Your METAbolic Rate Chapter 3: A Learning Laboratory Chapter 4: Our Journey to META Chapter 5: What's Your Current Pace?: A Diagnostic Section 2: The Acceleration Imperative Chapter 6: Accelerating Strategy: Less Plan, More Planning Chapter 7: Accelerating Organizations: Turning Drag into Drive Chapter 8: Accelerating Teams: Capability Equals Ability Minus Ego Chapter 9: Accelerating Leaders: The Leader Sets the Pace Section 3: How to Start Chapter 10: Finding the Right Recipe Chapter 11: The ABC of Behavior Change Chapter 12: Change the People or Change the People Chapter 13: The Board as Catalyst Section 4: The Four Key Skills Chapter 14: Ripple Intelligence: Join the Dots Chapter 15: Resource Fluidity: Match Resources to Opportunities Chapter 16: Dissolving Paradox: Reframe the Issue Chapter 17: Liquid Leadership: Connect Beyond Hierarchy Chapter 18: Conclusion: It's More than a Program Research Appendix Index.
Includes index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Organizational behavior; Strategic planning; Industrial management; Electronic books